2010
DOI: 10.1055/s-0030-1249373
|View full text |Cite
|
Sign up to set email alerts
|

Review of 793 Facial Fractures Treated from 2001 to 2008 in A Coruña University Hospital: Types and Etiology

Abstract: The purpose of this article is to analyze the incidence, demographic distribution, type, and etiology of all facial fractures treated by the Department of Oral and Maxillofacial Surgery in A Coruña University Hospital (Spain) from 2001 to 2008. A descriptive and analytic retrospective study evaluated 643 patients treated for facial fracture (excluding nasal and dento-alveolar) by the Department of Oral and Maxillofacial Surgery in A Coruña University Hospital from January 2001 to December 2008. Five parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
(28 reference statements)
3
10
1
Order By: Relevance
“…The symphysis and angle were the most common sites of multiple fractures followed by the symphysis and condyle. This finding was similar to other research studies6,7,13. Based on reports from other studies, the mandible angle fracture was the most frequent in cases of single fractures13, especially with assault-related fractures, and the symphysis and angle fractures were most common in multiple fractures5.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The symphysis and angle were the most common sites of multiple fractures followed by the symphysis and condyle. This finding was similar to other research studies6,7,13. Based on reports from other studies, the mandible angle fracture was the most frequent in cases of single fractures13, especially with assault-related fractures, and the symphysis and angle fractures were most common in multiple fractures5.…”
Section: Discussionsupporting
confidence: 94%
“…Other research reports showed similar results7. Assaults were the second most common factor while car accidents showed a relatively lower ratio with 74 patients (10.1%).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…[ [15][16][17] Our series included six female (8.7:1.3) patients. This high vulnerability of men to most types of trauma may be associated with the fact that in our society men have more freedom in outdoor activities and are more involved in high-risk jobs, thus being more vulnerable to accidents.…”
Section: Conflict-of-interest Issues Regarding the Authorship Or Artimentioning
confidence: 99%
“…Studies show that traffic collisions are among the leading causes of maxillofacial trauma [5,[7][8][9][10][11][12][13][14]17,18,20]. Notable subtypes of this type of trauma are incidents involving bicycles or motorcycles, which are represented at a significant percentage as etiological agents.…”
Section: Discussionmentioning
confidence: 99%